THE UNIVERSITY REVIEW IN ORDER OF HIGHER EDUCATION SOSIALIZATION in SMA ACEH BESAR - Ade Irfan; Anzora Anzora; Riki Musriandi (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2021)
The background of the implementation of this Community Service activity is the lack of understanding of students about the learning processes or lectures in universities. Most new students experience confusion with the lecture process at college. The Mathematics Education Lecturer Team at Abulyatama University FKIP saw this as a confused adaptation of new students in starting the lecture process in higher education. As a result, many new students lack confidence and lack the courage to express their creativity, abilities and even talents in the lecture process. The Lecturer and Student Team collaborated to introduce the lecture process in higher education to high school students in Aceh Besar by conducting campus surgery activities. The purpose of this activity is to introduce the learning process or lectures in higher education to class XII high school students in Aceh Besar. This activity is structured in the introduction of the campus, socialization of the path to higher education, the lecture process, as well as the delivery of the vision and mission of the Mathematics Education study program, FKIP Abulyatama University.Keywords: Campus Surgery, College, High School Students